(3agQSJ eDdaGJ GdSjhWis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3GdbGgQI s)
(3ChdgG (B:s
(3gPG agQSJ eDdaGJ TjNfG GdYdGeI TjN GdESdGe LdGd GdOjf YHO GdQMef GdCSjhWi eQJHG Ydi Gdafhf s
(3BNQgG (B:s
(3Gdecfhf ai JQLeI Pi Gdfhf BNQ eG fbdJ ef NW TjNfG GdeDdaq s
(3Vef eLehY , JQJjHgG (B: 3s
(3GdfSNI efbhdI Yf NW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3JHUQGJ GdCUd (B:s
Keywords: (3agGQS hecJHGJs